“We are the True Heirs of all the Splendor of Human Culture”: Stylistic Landmarks in the Monumental Painting of the USSR in the 1930s - Strukova, Alexandra I. (Actual Problems of Theory and History of Art, 2018)
The article considers both general issues related to the practice of Soviet artists in monumental painting, and the problem of mastering the heritage of art of past eras — one of the most relevant for the artistic process in the USSR in the 1930s.Special attention was paid to the development of wall painting and the training of mural artists throughout the whole decade. This was due not only to designing new public spaces (buildings, metro, exhibition pavilions), but, first of all, pursued propaganda goals. The panels and murals were included in the ensembles, endowed with a special suggestion due to the large size of canvases or frescoes, illusionistic pictorial techniques, the dioramic principle of constructing a single work and the whole ensemble, which, as it were, includes the viewer as part of a crowd embraced by a strong emotional impulse. To achieve the heyday of Soviet art (as well as the greatest psychological impact), it was necessary to use all available means: to combine the possibilities of different spatial arts (“the synthesis of the arts”), as well as the artistic achievements of the past.The examples of the ‘mastering’ of the art of antiquity, the Italian Renaissance, Old Russian wall painting, baroque, folk handicrafts on the example of Palekh painting, Art Nouveau, and also the art of the countries of the Far East by Soviet artists are considered successively in the article.A comparison with foreign practice shows that the adoption of retrospective stylizations corresponded to the global fashion, but it was Soviet art that strove for a comprehensive mastery of the world heritage and worked out on its basis images that were widely replicated in the future and formed a kind of Soviet canon. They can be called “the peaceful sky of the Soviet country”, “Soviet holiday”, the procession of the peoples of the USSR, etc.The field for experiments with stylization was reduced during the 1930s, in the 1940s the process ended in the dominance of official classicism.
Keywords: monumental painting; USSR in the 1930s; synthesis of arts; stylization; Soviet painting; heritage; All-Union Agricultural Exhibition; painting of Palekh; Chinese stylization; Vladimir Favorsky; Eugene Lanceray; Lev Bruni